2020
DOI: 10.1016/j.athoracsur.2019.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Early First-Generation Trifecta Valve Failure: A Case Series and a Review of the Literature

Abstract: Background. The Trifecta valve (Abbott, St Paul, MN) has excellent hemodynamic performance with acceptable rates of freedom from structural valve degeneration. However, some recent studies have reported early Trifecta valve failure. Here, we report a case series of seven Trifecta valve failures with a review of the literature. Methods. Of 107 implantations of Trifecta bioprostheses between 2012 and 2014, we encountered seven Trifecta valve failures (6.5%). Failure of a 19-mm Trifecta valve occurred in 1 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 20 publications
(51 reference statements)
1
38
1
Order By: Relevance
“…Trifecta failures as early as 3 months post-op have also been described before and attributed in part to insufficient surgeon experience with a new valve leading to PPM and higher postoperative peak and mean AV gradients, 20 and to mechanical issues: tear of the noncoronary cusp, circumferential pannus formation composed of fibrofatty tissue in the inflow portion, and leaflet calcification concentrated around the posts in the outflow portion leading to restricted leaflet mobility, stenosis, and regurgitation. 24,25 Valve size 19-21 mm has also been shown to contribute to PPM, but there was no preponderance for lower valve size in the early Trifecta failure group (Table 5). As such, the Trifecta failures were unlikely to be the result of valve size.…”
Section: Discussionmentioning
confidence: 99%
“…Trifecta failures as early as 3 months post-op have also been described before and attributed in part to insufficient surgeon experience with a new valve leading to PPM and higher postoperative peak and mean AV gradients, 20 and to mechanical issues: tear of the noncoronary cusp, circumferential pannus formation composed of fibrofatty tissue in the inflow portion, and leaflet calcification concentrated around the posts in the outflow portion leading to restricted leaflet mobility, stenosis, and regurgitation. 24,25 Valve size 19-21 mm has also been shown to contribute to PPM, but there was no preponderance for lower valve size in the early Trifecta failure group (Table 5). As such, the Trifecta failures were unlikely to be the result of valve size.…”
Section: Discussionmentioning
confidence: 99%
“…But, according to a recent study, the Trifecta valve had no hemodynamic superiority in maintaining a large valve orifice area over mid-and long-term periods while calcification and leaflet tear parameters were inferior to CEP (4). Some case reports on early leaflet tears in Trifecta valves (5,6) reported that a single leaflet tear may be causative for mild heart failure but two or more tears risks severe and catastrophic heart failure, necessitating an emergency operation (7). Similarly, both of our cases presented with acute dyspnea symptoms linked to rapid ruptures at two leaflets, with the second case especially requiring resuscitation and rapid operation.…”
Section: Commentmentioning
confidence: 59%
“…The Trifecta valve (Abbott, St Paul, MN, USA) has externally mounted leaflets that impart excellent hemodynamic performance compared to internal leaflets (3). However, early structural valve deterioration (SVD) has been recently reported in first-and second-generation valves (4)(5) (6). Here, we detail two catastrophic early SVD cases in Trifecta valves with multiple-leaflet tears.…”
Section: Introductionmentioning
confidence: 99%
“…With the Trifecta aortic bioprosthesis, the 6-year freedom from SVD and reoperation are 95% and 96%, respectively [30]. However, some reports of early Trifecta failure caused by cusp tears, early excessive pannus formation in the inflow portion, and leaflet calcification in the outflow portion have been described [31,32]. A study by Stubeda et al [33] showed that Trifecta aortic valves were associated with a significantly high risk of early reoperation in patients aged < 60 years and in patients that were current smokers.…”
Section: Discussionmentioning
confidence: 99%